2018
DOI: 10.5194/bg-15-1827-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variation pattern of particulate organic carbon and nitrogen in oceans and inland waters

Abstract: Abstract. We examined the relationship between, and variations in, particulate organic carbon (POC) and particulate organic nitrogen (PON) based on previously acquired ocean and inland water data. The latitudinal dependency of POC ∕ PON is significant between 20 and 90∘ N but weak in low-latitude areas and in the Southern Hemisphere. The mean values of POC ∕ PON in the Southern Hemisphere and Northern Hemisphere were 7.40±3.83 and 7.80±3.92, respectively. High values of POC ∕ PON appeared between 80–90 (12.2±7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 94 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…These higher nutrient ratios in freshwater ecosystems could be a general adaptation to the shorter residence time of water in freshwater systems than in marine systems. The influence of external inputs of organic matter and water, and the climatic conditions (volume of water inputs, evapotranspiration) of surrounding environments and the nearest terrestrial ecosystems can also vary greatly among and within sites over time, promoting high variability in C, N, and P concentrations and C:N:P ratios in inland water bodies (Zadereev et al, 2014;Collins et al, 2017;Huang et al, 2018,;Ngochera and Bootsma, 2018;Smith and Jarvie, 2018).…”
Section: Redfield Ratiomentioning
confidence: 99%
“…These higher nutrient ratios in freshwater ecosystems could be a general adaptation to the shorter residence time of water in freshwater systems than in marine systems. The influence of external inputs of organic matter and water, and the climatic conditions (volume of water inputs, evapotranspiration) of surrounding environments and the nearest terrestrial ecosystems can also vary greatly among and within sites over time, promoting high variability in C, N, and P concentrations and C:N:P ratios in inland water bodies (Zadereev et al, 2014;Collins et al, 2017;Huang et al, 2018,;Ngochera and Bootsma, 2018;Smith and Jarvie, 2018).…”
Section: Redfield Ratiomentioning
confidence: 99%
“…including perfluoroalkyl substances (Kothawala et al 2017). Riverine dissolved organic matter can produce carcinogenic disinfection by-products during the water treatment process (Baghoth et al 2011), and the ecological function of receiving water ecosystems depends on the chemical composition and bio-lability of carbon (Huang et al 2018;Song et al 2018). Large fluvial systems are the main arteries for the transfer of organic carbon to the ocean.…”
mentioning
confidence: 99%
“…Some DOM is released by living cells, but most of it is released upon cell death and lysis to the microbial community (Azam et al, 1983), leading to a peak in DOC coinciding or shortly after the peak in phytoplankton biomass or POC. Huang et al (2018), however, showed that the correlation between POC and DOC is strong for global, combined data of lakes, oceans and coastal waters but weak for individual water types. Accordingly, the correlation of POC and DOC was not strong at the Heiligendamm station.…”
Section: Relationships Between Organic Carbon and Nitrogen Fractionsmentioning
confidence: 95%